Building Capacity through Facilitated Conversations - Sarah Edwards (Academic Chairpersons Conference Proceedings, 2019)
While there is a national call for more training and support for department chairs who are positioned to have direct impact on faculty quality, only 3-4% report having received any type of formal training. Collectively sharing resources and facilitating conversations is a fiscally responsible way to support the development of all chairs and directors on a campus. This presentation will provide one institution’s journey and model for providing necessary training and support to chairs and directors.
Keywords: professional development; chairpersons; systems